The Mystic and the Theologian - Shideler, Mary McDermott (Theology today, 1975)
“Anyone who has ever gone to the zoo and tried to communicate with a hippopotamus knows the problem. It is simply impossible to get a word of sense out of the hippopotamus. The hippopotamus undoubtedly feels the same way about the human being. The consequence is that relations between human beings and hippopotamuses tend to be meaningless.”, —Russell Baker, “Try Saying Hello to a Helk,” The New York Times